INVESTIGATION OF TRANSITION ZONE OF INTERACTION BETWEEN ALUMINIUM AND NICKEL UNDER BRAZING CONDITIONS - A.A. CHULARIS; G.V. CHUMACHENKO; P.I. SELEZNEV (Advanced Engineering Research, 2006)
Structure of transition zone and mechanism of interaction between aluminium and nickel under brazing conditions are investigated.